Overview of June 2013 Flood and Landslides with focus on Darchula Disaster - Regmee, Shital Babu; Upadhyay, Surya Nath; Poudel, Prakash (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
In mid June 2013 there was a cloud outburst in northern Uttarakhanda, India and far western region of Nepal, due to simultaneous activation of monsoon arms one from Bay of Bengal in the east and other from the southwest. There was 322mm of rainfall in Uttarakhanda during the week 13-19 of June 2013 (847% of the nor-mal rainfall of Uttrakhanda for this period). The extreme ?ood event caused thousands of human lives lost and several billions of property damages in India and extensive damages in Nepal. The Mahakali River a border river between India and Nepal caused very heavy damages in several places in Nepal's Darchula and also in Dodhara and Chandhani, the Nepali settlements in west side Mahakali River. Contribution of Dhualiganga a tributary of the Mahakali River where a 280 MW hydro plant with 6.2 million cubic meters of storage reservoir capacity is constructed by India for the severity of flash flood in the region cannot be overlooked. The sudden spillway gate opening from this reservoir added the already very heavy floods in Mahakali that devastated Darchula the district HQ of Darchula. More than 100 houses in Darchula were washed away by the big flood event. However, India was quick to refute the charge of sluice-gate-opening of the Dam and stated that the disaster in Darchula was not caused by the dam opening. Detailed Investigation is yet to be done. This papers analyses the events surrounding the 17-18 June catastrophic flood causing wide spread damages in Darchula District Head Quarter. Both the countries need to work honestly for mutual benefit especially for minimising the effects of any disasters in the future. DOI: http://dx.doi.org/10.3126/hn.v13i0.10043 HYDRO NEPA LJournal of Water, Energy and Environment Issue No. 13, July 2013 Page: 57-63 Uploaded date: 3/13/2014